2014
DOI: 10.1007/7355_2014_48
|View full text |Cite
|
Sign up to set email alerts
|

Metabotropic Glutamate Receptor 2 Activators

Abstract: Schizophrenia is a common and severe, often disabling psychiatric illness of unknown aetiology that affects approximately 24 million people worldwide. The illness is characterized by symptomatology comprising positive symptoms (hallucinations and delusional behaviours), negative symptoms (anhedonia, social withdrawal and apathy) and cognitive dysfunction (diminished capacity for learning, memory and executive function). Current pharmacological treatments are effective at alleviating positive symptoms but have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 85 publications
(102 reference statements)
0
6
0
Order By: Relevance
“…The majority are structurally related to either LY487379 (2,2,2-trifluoro-N-[4-(2-methoxyphenoxy)phenyl]-N-(3-pyridinylmethyl)ethanesulfonamide hydrochloride) or BINA (biphenyl-indanone A), two prototypical mGlu 2 R PAMs ( Conn et al, 2009 ; Niswender and Conn, 2010 ). Many of these compounds are highly selective for mGlu 2 R and do not potentiate responses to activation of mGlu 3 R or any other mGluR subtype ( Cid et al, 2015 ). In addition, group II mGluR negative allosteric modulators (NAMs) have also been developed, but in this case acting at both mGlu 2 R and mGlu 3 R ( Hemstapat et al, 2007 ; Woltering et al, 2008a , b ).…”
Section: Group II Metabotropic Glutamate Receptorsmentioning
confidence: 99%
“…The majority are structurally related to either LY487379 (2,2,2-trifluoro-N-[4-(2-methoxyphenoxy)phenyl]-N-(3-pyridinylmethyl)ethanesulfonamide hydrochloride) or BINA (biphenyl-indanone A), two prototypical mGlu 2 R PAMs ( Conn et al, 2009 ; Niswender and Conn, 2010 ). Many of these compounds are highly selective for mGlu 2 R and do not potentiate responses to activation of mGlu 3 R or any other mGluR subtype ( Cid et al, 2015 ). In addition, group II mGluR negative allosteric modulators (NAMs) have also been developed, but in this case acting at both mGlu 2 R and mGlu 3 R ( Hemstapat et al, 2007 ; Woltering et al, 2008a , b ).…”
Section: Group II Metabotropic Glutamate Receptorsmentioning
confidence: 99%
“…This allowed defining BINA’s mechanism of action at the brain circuitry level where its effect was apparent in the prefrontal cortex, caudaute–putamen, nucleus accumbens, and mediodorsal thalamus, structures linked to schizophrenia [109]. After the introduction of LY487379 and BINA, a variety of structurally distinct classes of mGlu 2 R PAMs were discovered, many of which proved to have in vivo activity as well [110]. Early mutagenesis studies identified three amino acid residues in transmembrane (TM) segments IV and V of mGlu 2 R to be critical for the activity of LY487379 and several other mGlu 2 R PAMs [111, 112].…”
Section: Promise Of Mglur Positive Allosteric Modulatorsmentioning
confidence: 99%
“…Positive allosteric modulators (PAMs) offer an alternative approach toward mGluR2 activation with potentially significant advantages over orthosteric agonists . As exemplified by Merck and others , (Figure b), binding to the less homologous 7-transmembrane domain (7-TMD) leads to high subtype selectivity for mGluR2 and thus mitigation of mGluR3-mediated effects. This is significant, as previous studies in mouse models predictive of antipsychotic potential have shown that mGluR2, not mGluR3, mediates the actions of mGlu2/3 receptor dual agonists. , Furthermore, modulation restricts receptor activation only to relevant tissues in the presence of endogenous agonist (glutamate) and reduces the potential for tachyphylaxis, which has been reported with GPCR agonists upon chronic treatment …”
mentioning
confidence: 95%
“…With the rat FLIPR EC 50 of 18 measured to be 75 nM, the in vitro – in vivo correlation (IVIVC) was excellent. Furthermore, given the exposure required for full efficacy, 18 stands as one of the most efficacious orally dosed mGluR2 PAM’s to date in a rodent model applicable to clinically proven antipsychotics. ,, …”
mentioning
confidence: 99%